QTc Prolongation Risk Evaluation in Female COVID-19 Patients Undergoing Chloroquine and Hydroxychloroquine With/Without Azithromycin Treatment - Grewal, Sarah; Jankelson, Lior; van den Broek, Marcel P. H.; Cour, Martin; Bachmann, Gloria; Kostis, John B.; Misra, Kamana (Frontiers in Cardiovascular Medicine, 2020)
Women have higher risk for developing TdP in response to ventricular repolarization prolonging drugs. Hundreds of trials are administering chloroquine and hydroxychloroquine with/without azithromycin to COVID 19 patients. While an overall prolonged QTc has been reported in COVID-19 patients undergoing these treatments, the question on even higher QTc elevation risk in thousands of female COVID-19 patients undergoing these treatments remains unanswered. We therefore explore data reported and shared with us to evaluate safety and efficacy of antimalaria pharmacotherapies in female COVID-19 patients. Although we observed longer mean QTc intervals in female patients in 2 of the 3 cohorts reviewed, the sex disproportionality in COVID-19 hospitalizations precludes a clear sex mediated QTc interval elevation risk association in the female COVID-19 patients undergoing acute treatment regimens. Adoption of study designs that include observation of sex mediated differential triggering of cardiac electrical activity by these drugs is warranted.